2014
DOI: 10.1155/2014/835636
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Importance of Insects in Selenium Biogenic Cycling

Abstract: Selenium is an essential trace element for animal and human beings. Despite the importance of insects in most ecosystems and their significant contribution to the biological cycling of trace elements due to high abundance, population productivity, and diverse ecosystem functions, surprisingly little information is available on selenium bioaccumulation by these arthropods. This review considers selenium essentiality and toxicity to insects as well as insects' contribution to selenium trophic transfer through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…In insects, diets with supplemental selenium can benefit growth, survival, and reproduction, but higher concentrations can have the opposite effect 36,3840,46 . While insects play a role in the biogeochemical cycling of selenium 47,49 , little is known of the impact of selenium on predator–prey or host–parasitoid ecology; the biotransfer or biomagnification 50 of selenium can negatively affect the development and fitness of predators 51 , and higher concentrations of selenium can potentially disrupt host–parasitoid population dynamics, with Cotesia marginiventris (Cresson) (Hymenoptera: Braconidae) and the beet armyworm, Spodoptera exigua (Hubner) (Lepidoptera: Noctuidae), serving as an example 49,52 . Even though SeNPs have a lower toxicity and higher bioavailability than inorganic or organic forms of selenium 37 , applications of SeNPs ranging in concentration from 100–500 mg L −1 can still have significant entomotoxic effects 37,53 , including on the azuki bean beetle 33,34 (although its endosymbiont Wolbachia can mediate resistance 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In insects, diets with supplemental selenium can benefit growth, survival, and reproduction, but higher concentrations can have the opposite effect 36,3840,46 . While insects play a role in the biogeochemical cycling of selenium 47,49 , little is known of the impact of selenium on predator–prey or host–parasitoid ecology; the biotransfer or biomagnification 50 of selenium can negatively affect the development and fitness of predators 51 , and higher concentrations of selenium can potentially disrupt host–parasitoid population dynamics, with Cotesia marginiventris (Cresson) (Hymenoptera: Braconidae) and the beet armyworm, Spodoptera exigua (Hubner) (Lepidoptera: Noctuidae), serving as an example 49,52 . Even though SeNPs have a lower toxicity and higher bioavailability than inorganic or organic forms of selenium 37 , applications of SeNPs ranging in concentration from 100–500 mg L −1 can still have significant entomotoxic effects 37,53 , including on the azuki bean beetle 33,34 (although its endosymbiont Wolbachia can mediate resistance 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…There exists a delicate balance in the essential role of selenium as a micronutrient and its dosedependent toxicity in both vertebrate and invertebrate animals [40][41][42][43][44][45][52][53][54][55][56] . In insects, diets with supplemental selenium can benefit growth, survival, and reproduction, but higher concentrations can have the opposite effect 40,[43][44][45]53 .…”
Section: Discussionmentioning
confidence: 99%
“…Ever since revelation of Se's importance for mankind in 1974, there has been a steady increase in interest in this trace element. Modern Se investigations are characterized by examinations of Se in food chain of living organisms (Golubkina et al, 2014 ), biogeochemical cycling (Natasha et al, 2018 ), Se toxicity and deficiency (Schiavon & Vecchia, 2017 ). Moreover, the phenomenon of selenium protection against viral disorders has been extensively described in the light of the corona-virus pandemic (Zhang et al, 2020a , b , c ), implying that selenium supplementation could open up new avenues in COVID treatment, given that scientific evidence in China found that regions with high selenium levels had much reduced COVID morbidity and mortality.…”
Section: Physicochemical Characteristics and Toxicity/essentialitymentioning
confidence: 99%
“…Se has a great impact on insect physiology [38]. Studies showed that insects accumulate Se, but its effect on insect growth and survival is less investigated [35].…”
Section: Connection Between Selenium and Pestsmentioning
confidence: 99%